Business incubators the entrance of organizations to shift towards pioneering performance a study by a number of employees of the technical education organizations in mosul - علي, عبد الستار محمد; محمد, اثمار عبد الرزاق (Journal of Economics and Administrative Sciences, 2012)
The importance of this research is due to its importance goals, Which are about the attempt of researchers to investigate the probability of depending on businesses, environments to transform organizations, performance in away that enhance the leading  role of organizations  in their environments , and through views of a number of the staff working in the foundation of technical institutes in Mosul.  .     After deciding the methodology of the study that ,in one hand ,performs the goals of the study , and achieving a suitable theoretical framework to present the concepts of businesses, environments and the leading performance as well as to their dimensions . These concepts are regarded rare in the Iraqi library as far as the researchers know, especially in the field of leading performance .So this study is regarded the first attempt in this field. In their field framework the researchers analyzed data about the two variables of their study.  These data were collected by a five scale questionnaire. In their final analyses the researchers concluded that the businesses, environments could be regarded an important entrance to achieve the leading performance of organizations,     In conclusion the researchers presented their recommendations. Perhaps the most important of them, the recommendation directed to the respected organizations especially , and to Iraqi organizations in general to pay businesses, environment the needed attention through establishing suitable businesses, environment such as the one referred to in their theoretical framework of their research, in hope to contribute, through their services , to upgrade the Iraqi organizations to make them leading in their national markets, as well as to Arabic and Islamic markets.